Understanding and Exploiting the Effect of Tuberculosis Antimicrobials on Host Mitochondrial Function and Bioenergetics - Cahill, Christina; Phelan, James Joseph; Keane, Joseph (Frontiers in Cellular and Infection Microbiology, 2020)
Almost 140 years after its discovery, tuberculosis remains the biggest infectious disease globally. For half a century, patients with drug sensitive and drug resistant tuberculosis have undergone long, arduous and complex treatment processes with several antimicrobials that primarily function through direct bactericidal activity. Long-term utilization of these antimicrobials has been well characterized and associated with numerous toxic side-effects. With the prevalence of drug-resistant strains on the rise, and new therapies for tuberculosis urgently required, a more thorough understanding of these antimicrobials is a necessity. In order to progress from the ‘one size fits all’ treatment approach, understanding how these antimicrobials affect the function of host immune cells during tuberculosis infection may help to inform future studies, instigate discussion and help towards establishing personalized approaches to using such antimicrobials which could help to pave the way for more tailored treatment regimens. While recent research has highlighted the important role mitochondria and bioenergetics play in infected host cells, only a small number of studies have examined how these antimicrobials affect mitochondrial function and immunometabolic processes within these immune cells. This short review highlights how these antimicrobials affect key elements of mitochondrial function, leading to further discussion on how they affect bioenergetic processes, such as glycolysis and oxidative phosphorylation, and how antimicrobial-induced alterations in these processes can be linked to downstream changes in inflammation, autophagy and altered bactericidal activity.